Temeljne pravice in izzivi digitalizacije: Od pravne ureditve do prakse - Weingerl, Petra (2023)
Fundamental Rights and Challenges of Digitization: From Legal Regulation to Practice. The rapid development of digitization affects all areas of our lives. At EU level a broad ethical and legal debate has been taking place in the recent years, focusing particularly on artificial intelligence, internet of things, the role of tech giants and especially on appropriate regulatory framework that puts fundamental rights first. These questions were investigated closely as part of the Student Innovative Project for Social Benefit (ŠIPK) at the Faculty of Law University of Maribor with the cooperation of private non-profit institution, Zavod PIP, and eight students from the Faculty of Law, the Faculty of Economics and Business, the Faculty of Electrical Engineering, Computer Science and Informatics and the Faculty of Arts. The purpose of the project is to raise awareness among all social stakeholders about the impact of digitization on social relations and to prepare the basis for guidelines for the future regulation of digitization.
Keywords: digitization; artificial intelligence; ethical dilemmas; rule of law; discrimination; privacy